2021
DOI: 10.21037/atm-20-7690
|View full text |Cite
|
Sign up to set email alerts
|

Predictors associated with early and late restenosis of arteriovenous fistulas and grafts after percutaneous transluminal angiography

Abstract: Background: The objective of this study was to assess postintervention patency and analyze the predictive factors associated with early and late restenosis after intervention in hemodialysis arteriovenous fistulas (AVF) and arteriovenous grafts (AVG).Methods: This study retrospectively analyzed 284 hemodialysis patients who underwent percutaneous transluminal angioplasty (PTA) due to AVF and AVG stenosis. A total of 350 PTA procedures were performed. Clinical, anatomical, biochemical, and technical variables w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Although there have been several trials focused on DCB angioplasty in the treatment of arteriovenous fistula (AVF) stenosis, there has been controversy surrounding its efficacy and safety. The higher proportion of de novo AVF lesions noted in our trial were in line with what is currently observed in China, 2 and as such, we agree that this may have a positive impact on postangioplasty patency compared with recurrent lesions. In addition, many other factors besides the use of DCBs, such as characteristics of the study population and of the AVF-for example, AVF location, AVF age, and presence of calcification, diabetes, and intimal hyperplasia [3][4][5][6][7] -may also impact postangioplasty AVF patency and requires further study.…”
supporting
confidence: 91%
“…Although there have been several trials focused on DCB angioplasty in the treatment of arteriovenous fistula (AVF) stenosis, there has been controversy surrounding its efficacy and safety. The higher proportion of de novo AVF lesions noted in our trial were in line with what is currently observed in China, 2 and as such, we agree that this may have a positive impact on postangioplasty patency compared with recurrent lesions. In addition, many other factors besides the use of DCBs, such as characteristics of the study population and of the AVF-for example, AVF location, AVF age, and presence of calcification, diabetes, and intimal hyperplasia [3][4][5][6][7] -may also impact postangioplasty AVF patency and requires further study.…”
supporting
confidence: 91%
“…Several previous studies report factors associated with postintervention AVF patency, including patient age, AVF age, presence of diabetes, length of stenosis and the presence of residual stenosis 9 12. AVG patency is negatively associated with diabetes and low levels of serum albumin 13. Hypertension is positively associated with patency in patients with AVF14 and AVG13.…”
Section: Discussionmentioning
confidence: 95%
“…AVG patency is negatively associated with diabetes and low levels of serum albumin 13. Hypertension is positively associated with patency in patients with AVF14 and AVG13. In addition, patients with AVG access have a greater risk of patency loss than do those with AVF 15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average inflation pressure was 18 atm, and inflation pressures higher than the average did not significantly correlate with rupture risk in our study. Although the procedure for calibrating inflation pressures and the optimal inflation pressures are still under debate, inflating the balloon without high maximum pressure is one of the risk factors associated with the patency rate of AVF [20]. Other studies demonstrated no significant differences in rupture rates between low inflation pressures (10-14 atm) and high inflation pressures (24-30 atm) when dilating central venous stenosis in hemodialysis patients.…”
Section: Plos Onementioning
confidence: 99%